2013
DOI: 10.1039/c3sm50997d
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale transport of energy and mass flux during evaporation of liquid droplets into inert gas: computer simulations and experiments

Abstract: We use molecular dynamics (MD) simulations of a two-component Lennard-Jones (LJ) fluid to analyze the energy flux from an inert gas to the interface of an evaporating liquid droplet. Using this analysis we derive an analytical equation for the radius of the droplet, R(t), as a function of time, t. The formula is valid for evaporation of droplets of any material or size into the gas characterized by the mean free path, l, much larger than the molecular diameter, s. We find linear dependence R(t) $ t, for high l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 34 publications
4
44
0
Order By: Relevance
“…However unlike the condensation efficiency, the evaporation coefficient α may be greater than unity. This is supported by theoretical arguments and experiments [46], as well as recent Lennard-Jones numerical simulations of liquid droplet [47] and liquid slab evaporation [48]. Along with an equation of state, the Hertz-Knudsen equation provides the gas pressure, which appears also in the Rayleigh-Plesset equation (5).…”
Section: B Intermediate Growth Regime: the Rp-diffusion Systemmentioning
confidence: 57%
“…However unlike the condensation efficiency, the evaporation coefficient α may be greater than unity. This is supported by theoretical arguments and experiments [46], as well as recent Lennard-Jones numerical simulations of liquid droplet [47] and liquid slab evaporation [48]. Along with an equation of state, the Hertz-Knudsen equation provides the gas pressure, which appears also in the Rayleigh-Plesset equation (5).…”
Section: B Intermediate Growth Regime: the Rp-diffusion Systemmentioning
confidence: 57%
“…Our analytical model of evaporation used in this work was discussed in details in. 39,41,[47][48][49] It assumes rapid liquid mixing, implicating also no temperature gradients (which turns out to be a good approximation even for relatively fast evaporation rates 50 ) and makes use of the Köhler equation. 51 The Köhler equation formally requires a uniform distribution of particles in liquid, but this kind of parameterization reproduces the observed droplet evolution well.…”
Section: Evolution Of Droplet Sizementioning
confidence: 99%
“…shows an example of the evolution of the droplet radius of silica suspension found in experiment together with the numerical results from our evaporation model41,47 for pure water and for water with solid inclusions (fraction of inclusions ∼ 0.1% in volume).The experimental evolution was obtained with a combination of the Mie Scattering Lookup…”
mentioning
confidence: 98%
“…For water, many studies have reported α M through measurements of evaporation/condensation kinetics (Davies et al, ; Hołyst et al, ; Langridge et al, ; Marek & Straub, ; Miles et al, ; Raatikainen et al, ; Tsuruta et al, ; Winkler et al, ). Results from experiments using a variety of ensemble and single‐particle techniques confirm that α M is greater than 0.2 (Langridge et al, ; Miles et al, ) and even close to 1 (Davies et al, ; Raatikainen et al, ; Winkler et al, ).…”
Section: Introductionmentioning
confidence: 99%